Analisis Kerusakan Mesin Batching Plant di PT Duta Borneo Abadi Menggunakan Metode Hazard and Operability Study (HAZOP) - Dita Arum Sulistianingtyas; Novenda Kartika Putrianto (Teknik Industri Universitas Ma Chung, 2021)
PT. Duta Borneo Abadi is a company that produces large-scale concrete as their main product. In the production process, the main machine used is the batching plant machine. Due to its critical role, the batching plant machine has the potential for breakdowns, causing disruptions in the production process. Therefore, the identification and analysis of potential hazards are necessary, using the Hazard and Operability Study (HAZOP) method. HAZOP is a technique for identifying and analyzing deviations in the operation of the machine process. This study used machine damage data, machine maintenance data, pipe and instrument diagrams, and process flow diagrams. Based on the observations, six study points were identified to facilitate the identification of hazards, namely, the aggregate storage zone, weighing zone, delivery zone, cement storage zone, water storage and delivery zone, and mixing zone. The HAZOP worksheet analysis revealed 17 potential hazards, consisting of 15 low-risk hazards and 2 high-risk hazards. Based on the risk potential, recommendations for safeguards for each hazard and the creation of a daily checksheet to check machine components every month are proposed to prevent hazards from occurring.